Public optimism towards nanomedicine - Magrini A (Dove Medical Press, 2011)
Massimo Bottini1,2, Nicola Rosato2,3, Fulvia Gloria4, Sara Adanti4, Nunziella Corradino4, Antonio Bergamaschi5, Andrea Magrini41Sanford Burnham Medical Research Institute, La Jolla, CA, USA; 2Department of Experimental Medicine and Biochemical Sciences, University of Rome Tor Vergata, Rome, 3IRCCS-Neuromed Institute, Isernia, 4Department of Biopathology and Imaging Diagnostics, University of Rome Tor Vergata, Rome, 5Institute of Occupational Medicine, Catholic University of The Sacred Heart, Rome, ItalyBackground: Previous benefit–risk perception studies and social experiences have clearly demonstrated that any emerging technology platform that ignores benefit–risk perception by citizens might jeopardize its public acceptability and further development. The aim of this survey was to investigate the Italian judgment on nanotechnology and which demographic and heuristic variables were most influential in shaping public perceptions of the benefits and risks of nanotechnology.Methods: In this regard, we investigated the role of four demographic (age, gender, education, and religion) and one heuristic (knowledge) predisposing factors.Results: The present study shows that gender, education, and knowledge (but not age and religion) influenced the Italian perception of how nanotechnology will (positively or negatively) affect some areas of everyday life in the next twenty years. Furthermore, the picture that emerged from our study is that Italian citizens, despite minimal familiarity with nanotechnology, showed optimism towards nanotechnology applications, especially those related to health and medicine (nanomedicine). The high regard for nanomedicine was tied to the perception of risks associated with environmental and societal implications (division among social classes and increased public expenses) rather than health issues. However, more highly educated people showed greater concern for health issues but this did not decrease their strong belief about the benefits that nanotechnology would bring to medical fields.Conclusion: The results reported here suggest that public optimism towards nanomedicine appears to justify increased scientific effort and funding for medical applications of nanotechnology. It also obligates toxicologists, politicians, journalists, entrepreneurs, and policymakers to establish a more responsible dialog with citizens regarding the nature and implications of this emerging technology platform.Keywords: nanotechnology, nanomedicine, nanodrugs, benefit perception, risk perception, societal impact